Dynamic Changes in Pubic Symphysis and Superior Pubic Ligament During Pregnancy: A Study Using Ultrasound Shear-Wave Elastography - Chen P; Lin W (International Journal of Women's Health)
Peifen Chen,1 Wenqiang Lin2 1Department of Radiology, The First Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong Province, People’s Republic of China; 2Department of Ultrasound, The First Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong Province, People’s Republic of ChinaCorrespondence: Wenqiang Lin, The First Affiliated Hospital of Shantou University Medical College, 57 Changping Road, Shantou, Guangdong Province, 515041, People’s Republic of China, Tel +8615815086980, Email stronggerlin@163.comPurpose: This study aimed to analyze the morphology and elasticity of the pubic symphysis and superior pubic ligament during pregnancy using high-frequency ultrasound and shear-wave elastography, providing anatomical insights into pregnancy-related pelvic adaptations.Patients and Methods: A retrospective analysis included 202 participants, categorized into non-pregnant, first, second, and third trimester, and postpartum groups. Ultrasound and shear-wave elastography were employed to measure pubic symphysis width, superior pubic ligament length, thickness, and elasticity. Statistical comparisons were performed using one-way ANOVA and Tukey’s post-hoc tests.Results: Pubic symphysis width increased significantly from the second trimester (5.54 ± 1.24 mm) to peak in the third trimester (6.40 ± 2.06 mm, P < 0.001), remaining elevated postpartum (5.77 ± 1.62 mm). The SPL thickened (non-pregnant: 4.63 ± 1.12 mm vs third trimester: 8.22 ± 1.45 mm) and lengthened (23.74 ± 4.78 mm vs 40.54 ± 5.90 mm, P < 0.001) progressively. SWE revealed increased SPL elasticity in the third trimester (3.20 ± 0.50 cm/s, P < 0.001), declining postpartum (2.47 ± 0.28 cm/s). Elasticity correlated with SPL length in the first (*r* = 0.425) and third trimesters (*r* = 0.363) but not with age, PS width, or thickness (P > 0.05).Conclusion: This study is the first to evaluate dynamic morphological and elastic changes in the pubic symphysis and superior pubic ligament using high-frequency ultrasound and shear-wave elastography. The findings provide critical insights into pelvic adaptations during pregnancy and postpartum, offering valuable anatomical references for the clinical management of pregnancy-associated pelvic discomfort and dysfunction.Keywords: high-frequency ultrasound, shear wave elastography, pubic symphysis, superior pubic ligament, pregnancy-associated pelvic adaptations